A remarkable new species and additional novelties of Chamaedorea from Costa Rica and Panamá. Notables nuevas especies y novedades adicionales de Chamaedorea de Costa Rica y Panamá - Hodel, Donald R. (1997)
Three of the four new spp. of Chamaedorea (Arecaceae) described here are endemic (as far as is known) to Costa Rica. The "remarkable" one is C. piscifolia Hodel, G. Herrera & Casc., with simple, apically bifid and long-caudate, "fish-shaped" leaf-blades and infls. arising from the prostrate, often buried proximal portion of the stem. This is compared with the Guatemalan C. tuerckheimii (Dammer) Burret and, like that sp., has significant commercial potential. Because of that fact, the geographic range of C. piscifolia (and two of the other spp. described here) is deliberately concealed. The other new Costa Rican endemics are Chamaedorea incrustata Hodel, G. Herrera & Casc., most similar to C. pittieri L.H. Bailey, and C. rosibeliae Hodel, G. Herrera & Casc., compared especially with the sympatric C. anemophila Hodel. The type locality of C. rosibeliae is provided (Alto Urén, on the Atlantic slope of the Cordillera de Talamanca), presumably because it is so difficult of access. The remaining novelty, Chamaedorea rossteniorum Hodel, G. Herrera & Casc., is superficially similar to and has been confused with C. stricta Standl. & Steyerm., of northern Mesoamerica. However, the recent discovery of male flowers reveals that it is quite unrelated, belonging to a different subgenus. Chamaedorea rossteniorum has also been collected in Panama. All of the spp. are illustrated with superb color and black-and-white photos, mostly (except C. rosibeliae) of living specimens in the field